2021
DOI: 10.1097/md.0000000000024731
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab therapy intensification based on endoscopic activity is related to suppress treatment discontinuation in patients with Crohn disease

Abstract: Administering double doses of infliximab or shortening its dosing interval for patients with Crohn disease who experience a loss of response to treatment is an accepted treatment method; however, the effectiveness and appropriate timing of treatment intensification remain unclear. We examined the treatment outcomes of patients with Crohn disease receiving infliximab therapy intensification. Among 430 patients with Crohn disease who were seen at our related facilities from July 2002 to July 2018, 46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…€ Studies reporting 10 mg/kg were assumed to have dosing every 8 weeks. Source: [ 21 , 28 33 , 35 54 , 58 – 76 , 79 , 80 , 82 89 , 92 104 , 106 , 107 , 109 113 , 115 – 126 , 128 132 , 198 – 215 ] …”
Section: Resultsmentioning
confidence: 99%
“…€ Studies reporting 10 mg/kg were assumed to have dosing every 8 weeks. Source: [ 21 , 28 33 , 35 54 , 58 – 76 , 79 , 80 , 82 89 , 92 104 , 106 , 107 , 109 113 , 115 – 126 , 128 132 , 198 – 215 ] …”
Section: Resultsmentioning
confidence: 99%
“…However, more recent individual studies continue to provide conflicting perspectives. For example, a recent Japanese study of 46 CD patients followed up for 1 year following diminished infliximab effects after therapy intensification found that outcomes were improved in patients who received infliximab treatment intensification based on endoscopic findings of exacerbations to a greater extent than in patients monitored via clinical symptoms [ 110 ]. On the other hand, the recent STARDUST trial compared a treat-to-target strategy involving early endoscopy, regular biomarker and clinical symptom monitoring, with a clinical maintenance strategy in CD patients with moderate-to-severe disease receiving ustekinumab [ 111 ].…”
Section: Consensus Recommendationsmentioning
confidence: 99%